Comparison of four DNA extraction methods for the detection of Mycobacterium leprae from Ziehl–Neelsen-stained microscopic slides. Issue 4 (December 2015) - Ruiz-Fuentes, Jenny Laura; Díaz, Alexis; Entenza, Anayma Elena; Frión, Yahima; Suárez, Odelaisy; Torres, Pedro; de Armas, Yaxsier; Acosta, Lucrecia
Abstract: Objective/background: The diagnosis of leprosy has been a challenge due to the low sensibility of the conventional methods and the impossibility of culturing the causative organism. In this study, four methods for Mycobacterium leprae nucleic-acid extraction from Ziehl–Neelsen-stained slides (ZNS slides) were compared: Phenol/chloroform, Chelex 100 resin, and two commercial kits (Wizard Genomic DNA Purification Kit and QIAamp DNA Mini Kit). Methods: DNA was extracted from four groups of slides: a high-codification-slide group (bacteriological index [BI] ⩾ 4), a low-codification-slide group (BI = 1), a negative-slide group (BI = 0), and a negative-control-slide group (BI = 0). Quality DNA was evidenced by the amplification of specific repetitive element present in M. leprae genomic DNA (RLEP) using a nested polymerase chain reaction. Results: This is the first report comparing four different extraction methods for obtaining M. leprae DNA from ZNS slides in Cuban patients, and applied in molecular diagnosis. Good-quality DNA and positive amplification were detected in the high-codification-slide group with the four methods, while from the low-codification-slide group only the QIAGEN and phenol–chloroform methods obtained amplification of M. leprae . In the negative-slide group, only the QIAGEN method was able to obtain DNA with sufficient quality for positive amplification of the RLEP region. No amplification was observed in the negative-control-slide group by any method. Patients with ZNS negative slides can still transmit the infection, and molecular methods can help identify and treat them, interrupting the chain of transmission and preventing the onset of disabilities. Conclusion: The ZNS slides can be sent easily to reference laboratories for later molecular analysis that can be useful not only to improve the diagnosis, but also for the application of other molecular techniques.